The Formulation Impact of Investment-Hampering Regional Regulations Investment - Ray Ferza; Moh Ilham A Hamudy; M Saidi Rifki (Badan Strategi Kebijakan Hukum, 2019)
After the ruling of the Constitutional Court (MK), Ministry of Home Affairs (MoHA) and the Provincial Government can no longer revoke the problematic Regional Regulation (Perda) via an executive review. This situation, would increase the difficulty for MoHA to revise the investment-hampering regional regulations. The problematic Regulations includes of Karawang District's Perda No.1 of 2011 on the Management of Man Power and Bandung City's Perda No. 19 of 2012 on Disturbance Permit and Charges. Therefore, this study seeks to have a general understanding of the two regulations, the factors that influence the formulation, and to establish a guideline for the formulation of an ideal regional regulation. To achieve those objectives, this research used the descriptive qualitative method. The results of the study reveal that the formulation of regional regulation process is plagued by problems such as the absence of Academic Papers, the insufficient stakeholders' involvements, the lack of monitoring by the provincial government on the district/municipal regulation formulation process, lack of understanding of investment principles and confusion with the regional government control function. The various factors that cause the issuance of problematic regulations are, among others, the central government's regulatory packages, sociological elements, political elements, multi-interpretation in understanding the central government's regulation, as well as the fiscal capacity of the region. Therefore, the guidance of the Ministry of Home Affairs in supervising the regional government during the formulation process of districts/ municipal regulation related to investment is very much needed.